I Think, Therefore Eyeblink: The Importance of Contingency Awareness in Conditioning. (April 2016) - Weidemann, Gabrielle; Satkunarajah, Michelle; Lovibond, Peter F.
Can conditioning occur without conscious awareness of the contingency between the stimuli? We trained participants on two separate reaction time tasks that ensured attention to the experimental stimuli. The tasks were then interleaved to create a differential Pavlovian contingency between visual stimuli from one task and an airpuff stimulus from the other. Many participants were unaware of the contingency and failed to show differential eyeblink conditioning, despite attending to a salient stimulus that was contingently and contiguously related to the airpuff stimulus over many trials. Manipulation of awareness by verbal instruction dramatically increased awareness and differential eyeblink responding. These findings cast doubt on dual-system theories, which propose an automatic associative system independent of cognition, and provide strong evidence that cognitive processes associated with awareness play a causal role in learning.